REVIEW. Khapizov Sh.M., Shekhmagomedov M.G. Ibrahim-Haji from Urada (1701-1770) and his era: studies on history and life. Makhachkala, 2021. ISBN 978-5-6045929-0-8 - Mhitaran, Goar Zoraevna (History, Archeology and Ethnography of the Caucasus, 2021)
The present review discusses the collective monograph “Ibrahim-Haji from Urada (1701-1770) and his era: studies on history and life” (Makhachkala, 2021), which is a significant contribution to Caucasian studies. Given the fact that in recent years in historical science there has been an increased interest in the personality of Ibrahim-Haji al-Uradi, the comprehensive monograph sheds light on many aspects of the life and work of the outstanding scholar and expert in Islamic law and grammar of the Avar language, author of poems in Avar, theologian, one of the ideologists of the struggle between the Dagestanis and Nadir Shah, Qadi of Gidatl. The authors of the collective monograph, using a rich documentary base, carry out a scrupulous reconstruction of political events in the Caucasus of the period under study, and against this background analyze the life and work of Ibrahim-Haji al-Uradi. For the first time in modern Caucasian studies, the authors have introduced a number of Georgian, Turkish and Iranian primary sources, which help to reveal a more complete picture of the events in the Eastern Caucasus and the entire Caucasian region as a whole in the second half of the 18th century. Moreover, the authors attracted Arabic-language sources from private manuscript collections from Gidatl and the contents of the collections from the Collection of Oriental Manuscripts of the Institute of Archeology and Ethnography of the DFRC RAS. In addition to that, it is necessary to mention the private and mosque manuscript collections of Dagestan. In total, the authors have attracted more than 2000 works in their work. This study undoubtedly occupies a worthy place along with other works devoted to the life and work of Ibrahim-Hajji al-Uradi.
Keywords: East Caucasus; Dagestan; Caucasian studies; historical sources; Ibrahim-Hadzhi from Urada; review